1998
DOI: 10.1111/j.1439-037x.1998.tb00395.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature Effects on Germination and Viability of Weed Seeds in Soil

Abstract: The control of weeds by solar heating of the soil using transparent polyethylene (PE) sheets was studied in the field during the summers of 1994 and 1995. The maximum soil temperature under plastic cover at 5 cm depth averaged 53°C. At 5 cm soil depth, solarization increased temperature by about 9°C. In the non‐solarized soils, such high‐temperature days were fewer. A temperature of 55°C at 5 cm soil depths was recorded both in irrigated and non‐irrigated mulched soils. However, mulched soil recorded 70% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
3
10
1
Order By: Relevance
“…Clear plastic mulch raised soil temperature by 0.54-1.84 o C when compared to that of control. The increase in soil temperature due to solarization is lower than that reported by other researchers [26] [27]. This might be related to weather condition during solarization where the air temperature was 24-28 o C and during the experiment, the sky was cloudy most of the time.…”
Section: Resultscontrasting
confidence: 54%
“…Clear plastic mulch raised soil temperature by 0.54-1.84 o C when compared to that of control. The increase in soil temperature due to solarization is lower than that reported by other researchers [26] [27]. This might be related to weather condition during solarization where the air temperature was 24-28 o C and during the experiment, the sky was cloudy most of the time.…”
Section: Resultscontrasting
confidence: 54%
“…Several other studies examined the effect of solarization on M. indica . In New Delhi, India, Arora and Yaduraju (1998) reported that solarization for 30 days significantly reduced the number of several weedy species, whereas M. indica was not affected at all. Similarly, Yaduraju and Ahuja (1996) studied the effects of soil solarization on annual weed control and found the effects on C. rotundus and M. indica were not satisfactory, but the control of Avena sterilis ssp.…”
Section: Discussionmentioning
confidence: 99%
“…In non-crop areas, solarization has been used to manage A. fatua. Solarization using polyethylene sheets in a field study in India resulted in greater than 50% reduction (maximum of 85%) in germination of A. fatua seeds at 5-or 15-cm soil depths (Arora and Yaduraju 1998). The reduction was greater in moist soil than in dry soil.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 93%